The Endorsement Court - Jay D. Wexler (Washington University Journal of Law & Policy, 2006)
The Rehnquist Court was the first to apply the so-called “endorsement test” to evaluate the constitutionality of government-sponsored religious symbols and displays. The test asks whether a “reasonable observer” would feel that the government has sent “a message to non-adherents that they are outsiders, not full members of the political community, and an accompanying message to adherents that they are insiders, favored members of the political community.” Although the Supreme Court itself has applied the endorsement test in only a handful of cases, the test has played an extremely important role in how courts throughout the country have evaluated government action. Lower federal courts and state courts have applied the test in hundreds of cases to evaluate the constitutionality of many types of religious symbols and displays, from a Latin cross erected on a city water tower, to the “In God We Trust” inscribed on U.S. currency, to Mississippi’s state flag, to Ohio’s state motto. As such, the endorsement test is one of the Rehnquist Court’s most important Religion Clause innovations. The thesis of this Essay is two-fold. First, it argues that the majority bias critique is the most persuasive criticism of the endorsement test, followed (at some distance) by the contention that application of the test compromises the dignity of the federal courts. What unites these two critiques is that they focus not on the content of the endorsement test itself, but rather on the identity of the decision-maker applying the test. The Essay also proposes a possible radical solution to these two critiques by suggesting that Congress could create an Article I court staffed by experts in a wide range of majority and minority religious traditions. This court would decide endorsement challenges to religious symbols or displays, subject only to discretionary (but full) Supreme Court review. As this Essay notes, creation of such a tribunal would raise a variety of difficult constitutional (and other) issues, but such a proposal would, nonetheless, be worthy of Congress’ serious consideration.
Keywords: Religious symbols; Establishment clause (Constitutional law); Free exercise clause (Constitutional law); Standard of review (Law); Sandra Day O' Connor; 1930-; William H. Rehnquist; 1924-2005; United States. Supreme Court; Endorsements (Law); Freedom of religion; Religious symbolism; United States Constitution; United States